Revisiting the impact of direct taxes and transfers on poverty and inequality in South Africa - Mashekwa Maboshe; Ingrid D. Woolard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper uses a recent household survey and the CEQ framework to revisit and extend previous research on the impact of fiscal policy on income redistribution, and poverty in South Africa. We find, in accordance with previous research, that direct taxes and cash transfers are overall progressive and reduce inequality and poverty. Our disaggregated analyses, however, reveal that medical and interest tax benefits are regressive. We also find that certain social transfers provided to some minority population groups are not particularly well targeted. Periodically reviewing the effectiveness of fiscal policy at disaggregated levels would help to further improve the effectiveness of fiscal policy.
Keywords: D31; H22; H23; I38; 330; fiscal policy; fiscal incidence; direct taxes; social grants; inequality; poverty